Maritime Potential Analysis for Barru Regency Economic Development - Nursyahbani, A.Amirah; Akram, Ahmad Chusnul; Burhanuddin, Agussalim (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal